The comparison of Alfentanil and Remifentanil infusion during anesthesia on post-anesthesia recovery - Entezariasl, Masood (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND AND OBJECTIVE: With consideration the daily increased development of outpatient surgeries and high rate of these surgeries in elderly patients, rapid and safe recovery of patients is necessary. In this clinical trial study, recovery time and nausea and vomiting after the use of two rapid-onset narcotics, Alfentanil and Remifentanil, in elderly patients were evaluated. METHODS: In this double-blind prospective clinical trial, 40 elderly patients (age above 65 years) candidate to cataract surgery with general anesthesia were studied. The patients were divided randomly into two groups and for first group, 10 μg/kg of Alfentanil was injected and for second group Remifentanil 0.5 μg/kg was injected intravenously during 30 seconds one minute before induction. Both two groups were under general anesthesia with same method and during the anesthesia, first group took infusion of Alfentanil 1 μg/kg/min and second group took Remifentanil 0.1 μg/kg/min. In the end of surgery, the time intervals between end of anesthesia drug administration and spontaneous respiration, eyes opening with stimulation, verbal response and discharge of recovery room, also the incidence of complications related to narcotic drugs, especially nausea and vomiting, was recorded. The data were analyzed in SPSS software using descriptive and analytical statistics such as T-test and chi square test. RESULTS: The time of spontaneous respiration in Alfentanil group was 2 minutes and in Remifentanil group was 3.3 minutes, the difference was not statistically significant (P=0.08). The time of eyes opening with stimulation, verbal response, and discharge of recovery room were not significantly different. During recovery, incidence of nausea and vomiting in Remifentanil group (30% of patients) was significantly more than Alfentanil group (5% of patients) (P=0.045). CONCLUSIONS: Recovery time between Alfentanil and Remifentanil group was not significantly different, but incidence of nausea and vomiting in Remifentanil group was higher than Alfentanil group significantly. It seems that using Alfentanil in the anesthesia for surgical treatment of the elderly people can be preferred.